2016
DOI: 10.1038/srep37357
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of Zebrafish Ovarian Aromatase Gene (cyp19a1a) by TALEN and CRISPR/Cas9 Leads to All-male Offspring Due to Failed Ovarian Differentiation

Abstract: Sexual or gonadal differentiation is a complex event and its mechanism remains elusive in teleosts. Despite its complexity and plasticity, the process of ovarian differentiation is believed to involve gonadal aromatase (cyp19a1a) in nearly all species studied. However, most data concerning the role of aromatase have come from gene expression analysis or studies involving pharmacological approaches. There has been a lack of genetic evidence for the importance of aromatase in gonadal differentiation, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
119
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(128 citation statements)
references
References 71 publications
7
119
0
2
Order By: Relevance
“…The downregulation of T A B L E 1 Top 10 upregulated and downregulated genes in the Sets A and D of genes commonly expressed in ovaries of females exposed to elevated density or temperature | 61 cyp19a1a in ovaries was described in zebrafish exposed to elevated temperature (Ribas, Liew, et al, 2017) and to hypoxia conditions (Shang, Yu, & Wu, 2006), as well as in other fish species such as the olive flounder (Kitano, Takamune, Kobayashi, Nagahama, & Abe, 1999) and in the European sea bass (Díaz & Piferrer, 2015;Navarro-Martín et al, 2011) when subjected to HT. Thus, environmental stress reduced the expression of cyp19a1a in the gonads and this is in agreement with the observed masculinization since cyp19a1a is necessary for ovarian development, as demonstrated in the loss-offunction experiments (de Castro Assis, de Nóbrega, Gómez-González, Bogerd, & Schulz, 2018;Lau, Zhang, Qin, & Ge, 2016). In the testes, dmrt1, a transcription factor that plays a key role in male-sex determination in zebrafish (Webster et al, 2017), and amh, a gene involved in male sexual differentiation by suppressing the estrogen production (Rodríguez -Marí et al, 2005), did not show differences in gene expression due to HD confinement, suggesting no conspicuous effects of density at least in these two important genes for male sexual differentiation.…”
Section: Discussionsupporting
confidence: 86%
“…The downregulation of T A B L E 1 Top 10 upregulated and downregulated genes in the Sets A and D of genes commonly expressed in ovaries of females exposed to elevated density or temperature | 61 cyp19a1a in ovaries was described in zebrafish exposed to elevated temperature (Ribas, Liew, et al, 2017) and to hypoxia conditions (Shang, Yu, & Wu, 2006), as well as in other fish species such as the olive flounder (Kitano, Takamune, Kobayashi, Nagahama, & Abe, 1999) and in the European sea bass (Díaz & Piferrer, 2015;Navarro-Martín et al, 2011) when subjected to HT. Thus, environmental stress reduced the expression of cyp19a1a in the gonads and this is in agreement with the observed masculinization since cyp19a1a is necessary for ovarian development, as demonstrated in the loss-offunction experiments (de Castro Assis, de Nóbrega, Gómez-González, Bogerd, & Schulz, 2018;Lau, Zhang, Qin, & Ge, 2016). In the testes, dmrt1, a transcription factor that plays a key role in male-sex determination in zebrafish (Webster et al, 2017), and amh, a gene involved in male sexual differentiation by suppressing the estrogen production (Rodríguez -Marí et al, 2005), did not show differences in gene expression due to HD confinement, suggesting no conspicuous effects of density at least in these two important genes for male sexual differentiation.…”
Section: Discussionsupporting
confidence: 86%
“…Svensson et al (2016) described that anti-estrogen drugs (levonorgestrel and progesterone) could affect sexual development in juvenile fish, leading to a male phenotype. Additionally, it was reported that 100% mutant zebrafish developed to males when gonadal aromatase gene cyp19a1a (a key gene which regulates the synthesis of E2) was knocked out (Lau et al, 2016). Contrarily, promoted E2 and gene cyp19a in juvenile fish during the sex differentiation period after exposed to perfluorooctanesulphonic acid (Chen et al, 2016) or monocrotophos (Gao, 2011) produced a female-biased sex ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Fish are handled following standard practices 29 and guidelines from the Institutional Animal Care and Use Committee (IACUC) in the Mayo Clinic (A34513-13-R16, A8815-15). Adult zebrafish are kept in a 9 L (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) fish) or 3 L housing tanks (10-15) at 28.5 C with a light/dark cycle of 14/10 hours. Zebrafish gonads begin developing around 15 dpf (daypost fertilization).…”
Section: Zebrafish Husbandrymentioning
confidence: 99%
“…30 A multifactorial sexual differentiation process involving multiple genes and environmental factors takes place around 25 dpf and is considered completed around 60 dpf. [31][32][33] Sexes are not determined in larval fish (5 dpf ) in this study. intensity.…”
Section: Zebrafish Husbandrymentioning
confidence: 99%